Chemical Composition and Acaricidal Activity of Lantana camara L. Essential Oils Against Rhipicephalus microplus - Jorge Ramírez; Karla Balcázar; Jéssica López; Leydy Nathaly Castillo; Ruth Ortega; Haydee Vidal López; Ernesto Delgado-Fernández; Wilmer Vacacela; James Calva; Chabaco Armijos (Plants)
For the first time, essential oils (EOs) from the leaves and flowers of Lantana camara L., grown in Loja, Ecuador, have been isolated by steam distillation and analyzed. The oil yields from the extractions were 0.021 and 0.005% for the leaves and flowers, respectively. A compositional analysis using gas chromatography revealed the presence of EOs, comprising approximately 97.98% of the extract from the leaves and 74.58% of the extract from the flowers. The chemical characterization of these EOs indicated sesquiterpenic profiles. The most representative constituents of the essential oils from the flowers were γ-Curcumene (21.79%), (E, E)-α-Farnesene (20.07%), and α-Zingiberene (13.38%), while the EOs from the leaves were characterized by the abundant presence of γ-Curcumene (21.87%), (E)-Nerolidol (15.09%), and cis-Muurola-4(14),5-diene (12.65%). Furthermore, the acaricidal efficacy of the EOs from the leaves of L. camara was tested by a dip test with adult ticks, resulting in acaricidal efficacy at concentrations of 10%, demonstrating the useful properties of these EOs.